Development and initial validation of the Comprehensive Geriatric Oral Health Assessment Tool - Shervan Shoaee; Mohammad‐Hossein Heydari; Hossein Hessari; Neda Mehrdad; Laleh Khalilazar; Bahareh Hatami; Farshad Sharifi (Wiley, 2023)
Abstract Objectives Improving the oral health of the elderly is crucial to improving their general health and quality of life. To reach this goal, it is necessary to start with a comprehensive oral health assessment and a detailed treatment plan. The aim of this study was, therefore, to develop a comprehensive Oral Health Assessment Tool for the geriatric population. Material and Methods Following a panel of experts' consultation, a clinical form and a self‐assessment questionnaire were developed, encompassing eight domains: dental caries, periodontal diseases, partial and complete edentulism, oral soft tissue lesions, occlusion, xerostomia, temporomandibular joints, and oral or oral prostheses hygiene. Subsequently, a pilot study was conducted to appraise the clinical form and questionnaire involving 84 residents of an Iranian nursing home. After securing ethics approval, both the qualitative and quantitative aspects of the self‐assessment questions' validity and reliability were assessed, and specificity and sensitivity were calculated. Results The mean age of the participants was 69.8 (±4.1) years, and 86% had less than 12 years of education. The questions regarding the number of remaining teeth and the number of decayed teeth had the highest sensitivity (97% and 88%), respectively. Questions regarding the presence of periodontitis and gingivitis had the highest specificity (both 100%). Conclusions A Comprehensive Geriatric Oral Health Assessment Tool has been developed and its validity and reliability evaluated in a pilot study. It should now be further evaluated in larger studies.